2012
DOI: 10.1063/1.3673596
|View full text |Cite
|
Sign up to set email alerts
|

Resistive pulse sensing of magnetic beads and supraparticle structures using tunable pores

Abstract: Tunable pores (TPs) have been used for resistive pulse sensing of 1 lm superparamagnetic beads, both dispersed and within a magnetic field. Upon application of this field, magnetic supraparticle structures (SPSs) were observed. Onset of aggregation was most effectively indicated by an increase in the mean event magnitude, with data collected using an automated thresholding method. Simulations enabled discrimination between resistive pulses caused by dimers and individual particles. Distinct but time-correlated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(57 citation statements)
references
References 83 publications
1
56
0
Order By: Relevance
“…For example, Willmott et al used magnetic fields to cause aggregation and increased translocation rates of super-paramagnetic beads with blockades characterized by multiple overlapped peaks and thus overall increased TD. 54 However, in the current study, the overall particle concentration (and thus translocation rate) decreases with eNP swelling (Fig. 11) thus making the likelihood of multiple, nearly simultaneous, overlapping translocations negligible.…”
Section: Resultsmentioning
confidence: 52%
“…For example, Willmott et al used magnetic fields to cause aggregation and increased translocation rates of super-paramagnetic beads with blockades characterized by multiple overlapped peaks and thus overall increased TD. 54 However, in the current study, the overall particle concentration (and thus translocation rate) decreases with eNP swelling (Fig. 11) thus making the likelihood of multiple, nearly simultaneous, overlapping translocations negligible.…”
Section: Resultsmentioning
confidence: 52%
“…31 As with all RPS sensors the only consumable is the tunable pore, eliminating the need for a carrier gas, fluidics, or optics. TRPS has been validated to accurately determine the concentration, size and surface charge of dispersed inorganic particles 24,[32][33][34][35][36][37] as well as the concentration of a range of biological analytes, which have been reviewed previously. 38,39 Conical nanopores, as used within TRPS, exhibit ionic rectification properties.…”
Section: Introductionmentioning
confidence: 99%
“…The authors concluded that the system demonstrates promise as an effective drug vehicle in targeted and controlled inhalation therapy. The ability of TRPS to characterise SPIONs was also studied by Willmott and colleagues [18,70]. SPIONS are widely used in molecular identification, purification, separation and aggregation.…”
Section: Trps In Drug Delivery and Drug Development Applicationsmentioning
confidence: 98%
“…TRPS is an adaptation of RPS in which utilises a conical tunable elastomeric pore that can be stretched or relaxed to change the pore size to suit the sample [11,13,[15][16][17][18][19]. Tunable pore membranes are made of thermoplastic polyurethane and the pores are introduced by mechanical puncture.…”
Section: Tunable Resistive Pulse Sensing (Trps)mentioning
confidence: 99%
See 1 more Smart Citation